Synthesis and Characterization of Architecturally Modified Mesoporous-Microporous MFI (Mobil Five) Zeolite with Enhanced Catalytic Activity - Mani Pathak1, Dhanju; Kumar Ghosh2, Pankaj; Kr Shah3, Kishor; Kumar Talukdar4, Anup (Asian Journal of Chemistry, 2021)
Four samples of MFI zeolites with silica to alumina ratio of 100 and using different silica to carbon mass ratios (1:1, 1:4, 1:8 and 1:12) were synthesized by using carbon black particles. Silica-alumina molar ratio imposes the framework structure to the synthesized zeolites. In general with an increase in the silica-alumina molar gel ratio, the thermal stability, acid resistance and hydrophobicity of the product increases and ion-exchange capacity decreases. A higher molar ratio (as high as 100) of silica to alumina is considered. ZSM-5 zeolites being mainly microporous, their use as catalyst is restricted only to small molecules. So, by introducing mesopores in zeolite framework, we basically tried to overcome the limited use of ZSM-5 in reactions involving large molecules. Pore structure of ZSM-5 can be modified by using carbon black particles during synthesis. Such type of synthesis can be used to introduce the mesopore and to decrease the crystal size of ZSM-5 zeolite. Different silica to carbon mass ratio is used to study the pore structure and crystal size of ZSM-5 zeolites under autogeneous pressure without adding any promoter or organic solvent. The synthesized samples were characterized by different techniques such as X-ray diffraction, FTIR spectroscopy, scanning electron microscopy, TGA and N2 adsorption-desorption isotherm. The samples exhibit high crystallinity (84-91%). The particle size ranged from 2.8 to 7.3 μm. Mesopore to micropore ratios was found to increase with increasing silicon to carbon mass ratio. These structurally modified meso-micro zeolite showed enhanced activity in the benzyl alcohol esterification reaction using acetic acid. The selectivity towards benzyl acetate in all the cases was found to be 100%.